Cosmology and eschatology in Hebrews the settings of the sacrifice - Schenck, Kenneth 1966- (Cambridge Cambridge University Press, 2007)
Scholars argue over where Hebrews fit in the first century world. Kenneth L. Schenck works towards resolving this question by approaching Hebrews' cosmology and eschatology from a text-orientated perspective. After observing that the key passages in the background debate mostly relate to the 'settings' of the story of salvation history evoked by Hebrews, Schenck attempts to delineate those settings by asking how the 'rhetorical world' of Hebrews engages that underlying narrative. Hebrews largely argue from an eschatology of two ages, which correspond to two covenants. The fresh age has come despite the continuance of some old age elements. The most characteristic elements of Hebrews' settings, however, are its spatial settings, where we find an underlying metaphysical dualism between the highest heaven, which is the domain of spirit, and the created realm, including the created heavens. This creation will be removed at the eschaton, leaving only the unshakeable heaven.
The quest for the historical Hebrews -- The rhetorical strategy of Hebrews -- The settings of the story in time -- The destiny of humanity -- The two ages -- The settings in space -- The spatial dualism of Hebrews -- The heavenly tabernacle in Hebrews
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible -- Criticism, interpretation, etc; Eschatology -- Biblical teaching; Biblical cosmology; Bible ; Hebrews ; Criticism, interpretation, etc; Eschatology ; Biblical teaching